Factors contributing to paddy farmers' intention to participate in agriculture Takaful / Nurul Aien Abd Aziz - Abd Aziz, Nurul Aien (2014)
The agriculture sector is an economic sector that exposed to an array of risks such as climate change, pest's attack, disease and others. In its attempt to sustain and protect this sector, the Malaysian government in its 2013 budget has initiated a Takaful plan to help farmers reduce losses resulting from natural disasters. Hence, this research aims to investigate the relationships between Attitude, Subjective Norm, Perceived Behavioral Control, Perceived Risk, Knowledge and Intention to Participate in Agriculture Takaful. Apart from this, the research also aims to investigate the relationship of demographic characteristics which are Age, Size of paddy field, and Level of education and Level of income on the intention to participate in Agriculture Takaful. 336 respondents comprising paddy farmers in Kedah participated in this survey. Stratified random sampling technique was used to measure the Attitude, Subjective Norm, Perceived Behavior Control, Perceived Risk and Intention to participate in Agriculture Takaful. Pearson correlation was used to measure the relationship between the variables. The results indicated insignificant relationships between all the demographic variables and intention to participate in Agriculture Takaful. Furthermore, the findings also explained that Perceived Behavior Control, Perceived Risk and Attitude are the significant determinants that influenced paddy farmers' intention to participate in Agriculture Takaful. Findings from the study would be beneficial to Takaful operators, relevant government agencies and policy makers to promote an Agriculture Takaful plan for this sector.